2022
DOI: 10.1371/journal.pone.0268136
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic forefoot and heel stiffness across consecutive foot stiffness categories and sizes

Abstract: Prosthetic foot stiffness plays a key role in the functional mobility of lower limb prosthesis users. However, limited objective data exists to guide selection of the optimal prosthetic foot stiffness category for a given individual. Clinicians often must rely solely on manufacturer recommendations, which are typically based on the intended user’s weight and general activity level. Availability of comparable forefoot and heel stiffness data would allow for a better understanding of differences between differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Then, we fit linear and quadratic least-squares curves to the normal force-displacement and torque-angle data from the loading phases of the last three cycles for each prosthetic foot at the heel, midfoot, and forefoot. So that our results are comparable to previous studies that characterized Vari-flex prosthetic feet (the higher profile version of the LP Vari-flex prosthesis) ( 11 , 20 ), we calculated average axial and torsional stiffness values from the discrete value of the slope of the force-displacement and torque-angle curve from a minimum value of 50 N to 1.0 × body weight (BW) for the average body mass recommended for the moderate impact level ( Table 1 ). We averaged that value for the last three test cycles for each foot and test condition.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Then, we fit linear and quadratic least-squares curves to the normal force-displacement and torque-angle data from the loading phases of the last three cycles for each prosthetic foot at the heel, midfoot, and forefoot. So that our results are comparable to previous studies that characterized Vari-flex prosthetic feet (the higher profile version of the LP Vari-flex prosthesis) ( 11 , 20 ), we calculated average axial and torsional stiffness values from the discrete value of the slope of the force-displacement and torque-angle curve from a minimum value of 50 N to 1.0 × body weight (BW) for the average body mass recommended for the moderate impact level ( Table 1 ). We averaged that value for the last three test cycles for each foot and test condition.…”
Section: Methodssupporting
confidence: 91%
“…In general, we found that the heel and forefoot axial stiffness values of the LP Vari-flex prosthetic foot for a given stiffness category are stiffer than the higher profile Vari-flex prosthetic foot model. For example, the average axial stiffness value of the heel for a size 27 LP Vari-flex without a shoe ranges from 49.1 to 58.7 kN/m for categories 5–7, whereas the average axial stiffness value of the heel for a size 27 Vari-flex prosthetic foot without a shoe ranges from 37.5 to 45.4 kN/m in Turner et al ( 20 ) and 36.4 to 47.1 kN/m in Ruxin et al ( 11 ) for categories 5–7. Moreover, the average axial stiffness value of the forefoot for a size 27 LP Vari-flex without a shoe ranges from 36.2 to 47.0 kN/m for categories 5–7, whereas the average axial stiffness value of the forefoot for a size 27 Vari-flex prosthetic foot without shoes for categories 5–7 ranges from 29.1 to 38.5 kN/m in Turner et al ( 20 ) and 28.6 to 40.0 kN/m in Ruxin et al ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The PDAP mechanism is paired with a custom-compliant low-profile foot designed using the methods described in Bartlett et al ( 2022b ). The foot was selected to have a comparable stiffness to prosthetic feet prescribed at the K3 activity level (Turner et al, 2022 ). The device (including compliant foot) has a mass of 620 g and a build height of 8.5 cm, which is comparable to many commercially available ESR feet (Bartlett et al, 2022b ).…”
Section: Designmentioning
confidence: 99%
“…These values will inform dynamic function and can be implemented in future prosthetic design. Previous studies have characterized the mechanical properties of passive-elastic prosthetic feet (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and found that they are well described by linear (11,14) or curvilinear (9,13,(15)(16)(17) force-displacement and torque-angle profiles, which are used to calculate axial (kN/m) and torsional (kN*m/rad) stiffness values. These studies provide axial stiffness values for forces applied to a prosthetic foot heel, midfoot, and forefoot.…”
Section: Introductionmentioning
confidence: 99%